Horrid Hanry jolly joke book - "Simon, Francesca" (Orion children's books: China, 2008)
Q: What hangs out your underpants? A: We don't know, but wet yourself laughing at HORRID HENRY'S JOLLY JOKE BOOK. It's even funnier and even grosser than the last one!
Keywords: Joks